Implementation of Cancer Control Programs, Cancer Prevention Research - Moore, Malcolm A (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45479147/Implementation-of-Cancer-Control-Programs-Cancer-Prevention-Research